Perbandingan Minat Belajar PAI Siswa Pada Pembelajaran Offline Sebelum dan Sesudah Pandemi di SMAN 5 Bukittinggi - Arif Aulia Rizki; Wedra Aprison (ALFIHRIS : Jurnal Inspirasi Pendidikan, 2023)
The background to this research is the Covid-19 pandemic, which previously had shaken all sectors in the world, including the education sector itself, where the learning process has changed to online learning. In online learning, there are many efforts that must be made, but not all students can accommodate the needs of learning implementation services and ultimately have an impact on student learning interest. Currently learning has been carried out offline again, because now it has entered the new normal period. This study aims to compare students' interest in studying PAI during offline learning before and after the pandemic. This type of research is descriptive comparative with a quantitative approach, the population of all class X students is 334 students, the total sample is 47 students using simple random sampling technique. The data collection technique is a questionnaire with descriptive and inferential data analysis techniques. The results of the study were that students' interest in learning PAI was higher when learning was offline before the pandemic with a percentage of 70% in the medium criteria as evidenced by the t-test at a significant level of 5%, obtained t count > t table (3.00 > 2.012) so that Ha is accepted.